MBNQA Approach in Quality Management Supporting Sustainable Business Performance in Agribusiness - Radovan Savov; Juraj Chebeň; Drahoslav Lančarič; Roman Serenčéš (Amfiteatru Economic Journal, 2017)
Despite attention being paid to quality management in the literature, little empirical research has been conducted on developing the link between adoption of quality management approach and business performance in agricultural enterprises, and moreover, only a few empirical studies have investigated this issue in Central and Eastern Europe. The conducted empirical survey examines the relationship between adopting the quality management approach and business performance from the perspective of agricultural enterprises in Slovakia. The empirical findings are based on 70 responses from agribusinesses in Slovak Republic. To measure the adopting of quality management approach the MBNQA model was used. The authors have used linear regression as an evaluation method. Based on the results it can be concluded the adopting of quality management approach is determined by ownership. The enterprises owned by the owner from abroad adopt the quality management approach more readily than the domestic ones. The size of the enterprise and type of production do not determine the adopting of quality management approach in the agricultural enterprises in the Slovak Republic. This study contributes to the European research that studies the relation between quality management and business performance of agribusinesses by means of an empirical investigation in agricultural organizations in a transition economy such as Slovakia.
Keywords: Q13; M11; O13; 330; MBNQA model; quality management; business performance; agribusiness